Real-World Effectiveness of Remdesivir in Adults Hospitalized With Coronavirus Disease 2019 (COVID-19): A Retrospective, Multicenter Comparative Effectiveness Study. (15th December 2021) - Garibaldi, Brian T; Wang, Kunbo; Robinson, Matthew L; Betz, Joshua; Caleb Alexander, G; Andersen, Kathleen M; Joseph, Corey S; Mehta, Hemalkumar B; Korwek, Kimberly; Sands, Kenneth E; Fisher, Arielle M; Bollinger, Robert C; et al.
Abstract: Background: There is an urgent need to understand the real-world effectiveness of remdesivir in the treatment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Methods: This was a retrospective comparative effectiveness study. Individuals hospitalized in a large private healthcare network in the United States from 23 February 2020 through 11 February 2021 with a positive test for SARS-CoV-2 and ICD-10 diagnosis codes consistent with symptomatic coronavirus disease 2019 (COVID-19) were included. Remdesivir recipients were matched to controls using time-dependent propensity scores. The primary outcome was time to improvement with a secondary outcome of time to death. Results: Of 96 859 COVID-19 patients, 42 473 (43.9%) received at least 1 remdesivir dose. The median age of remdesivir recipients was 65 years, 23 701 (55.8%) were male, and 22 819 (53.7%) were non-White. Matches were found for 18 328 patients (43.2%). Remdesivir recipients were significantly more likely to achieve clinical improvement by 28 days (adjusted hazard ratio [aHR] 1.19, 95% confidence interval [CI], 1.16–1.22). Remdesivir patients on no oxygen (aHR 1.30, 95% CI, 1.22–1.38) or low-flow oxygen (aHR 1.23, 95% CI, 1.19–1.27) were significantly more likely to achieve clinical improvement by 28 days. There was no significant impact on the likelihood of mortality overall (aHR 1.02, 95% CI, .97–1.08). Remdesivir recipients on low-flow oxygen were significantly less likely to die than controls (aHR 0.85, 95% CI, .77–.92; 28-day mortality 8.4% [865 deaths] for remdesivir patients, 12.5% [1334 deaths] for controls). Conclusions: These results support the use of remdesivir for hospitalized COVID-19 patients on no or low-flow oxygen. Routine initiation of remdesivir in more severely ill patients is unlikely to be beneficial. Abstract : Remdesivir was significantly associated with an increased likelihood of clinical improvement in patients on no or low-flow oxygen and a reduction in mortality among individuals on low-flow oxygen. Routine use of remdesivir in sicker patients is unlikely to be beneficial.